Cultural Policy: Some initiatives and trends to manage cultural diversity in Indonesia - Purwanto, Semiarto Aji (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
This article discusses the cultural policy in the state level. The discussion on cultural policy cannot be separated from the idea of ​​the state's interest in maintaining citizens' trust in government programs. The strong role of the state in formulating cultural policies is often seen as the hegemony of the state over society, in the perspective of governmentality, as if the state has the power to determine what its citizens may do.  In Indonesia, cultural policies have also been tried to be implemented from time to time. However, some of our cultural policies tend to look at the macro and general aspects. Local initiatives are indeed seen, but in the end, macro ideas are taken into consideration. Besides being aimed at tourism, the development of local culture is also carried out by referring to certain standards that come from outside the community context. One of the standards that is currently popular is to identify a tradition and then trying to convince the public that the tradition has the right to be included in the category of national intangible cultural heritage.  I try to reformulate cultural policies, in the context of Indonesia, which has diverse traditions, amid this global change, as an effort to maintain the dynamic of local traditions. It can be pursued primarily by protecting traditional (adat) communities and their cultural works. It is not a question of 'extinction' or 'sustainability' but how these traditions can develop in the community, become part of the community, and rediscover its relevance to conditions outside the rapidly growing community.